2023
DOI: 10.3126/ajms.v14i9.54891
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, acceptance, and hesitancy about COVID-19 vaccine among residents of urban and rural health training center field practice area of a medical college at Kolkata: A cross-sectional survey

Sonali Sain,
Amitabha Chattopadhyay,
Dibakar Haldar

Abstract: Background: Effective vaccination is a successful tool for controlling COVID-19 pandemic, along with other preventive measures. Both intention to get vaccinated and barrier to vaccination played important role in COVID vaccination drive. Aims and Objectives: The present study was conducted to assess awareness, acceptance, and hesitancy about COVID-19 vaccine among the residents of rural and urban area and to assess the factors related to their attitude. Materials and Methods: A descriptive cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This is also seen in males being more vaccinated compared to females. Several scholars have reported that poor health outcomes in any population are primarily associated with disparities in socioeconomic conditions and poor educational levels [31][32][33] . This fundamental gap leads to unaffordable, inaccessible, poor quality, and sceptical thoughts regarding modern healthcare services 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…This is also seen in males being more vaccinated compared to females. Several scholars have reported that poor health outcomes in any population are primarily associated with disparities in socioeconomic conditions and poor educational levels [31][32][33] . This fundamental gap leads to unaffordable, inaccessible, poor quality, and sceptical thoughts regarding modern healthcare services 34,35 .…”
Section: Discussionmentioning
confidence: 99%